Punitiveness of society and criminal policy in six Central European countries - Ostaszewski, Paweł (European journal of criminology, 2024)
The countries of Central Europe are home to diverse penal cultures but rare comparative studies typically focus only on national penal codifications or on cross-country measures of public attitudes towards crime and punishment. This article compares three dimensions of punitiveness ? penal legislation, actual sentencing practice of the courts, and punishment preferences of the general public ? in six jurisdictions: Austria, Czechia, Germany, Hungary, Poland, and Slovakia. Punishment preferences features new data from the Central European Social Survey, in which respondents were asked to recommend suitable sentences for five hypothetical crimes. We found public preferences relate closely to the domestic judicial practice but less so to the maximum penalties provided in a country's penal code. In particular, participants based in Germany proved far less punitive than others, which echoes the penal moderation of German courts.